Synergistic effect of phosphorothioate, 5′-vinylphosphonate and GalNAc modifications for enhancing activity of synthetic siRNA. Issue 12 (15th June 2016) - Prakash, Thazha P.; Kinberger, Garth A.; Murray, Heather M.; Chappell, Alfred; Riney, Stan; Graham, Mark J.; Lima, Walt F.; Swayze, Eric E.; Seth, Punit P.
Graphical abstract: Abstract: Chemical modifications are essential to improve metabolic stability and pharmacokinetic properties of siRNA to enable their systemic delivery. We investigated the effect of combing the phosphorothioate (PS) modification with metabolically stable phosphate analog ( E )-5′-vinylphosphonate and GalNAc cluster conjugation on the activity of fully 2′-modified siRNA in cell culture and mice. Our data suggest that integrating multiple chemical approaches in one siRNA molecule improved potency 5–10 fold and provide a roadmap for developing more efficient siRNA drugs.